Shuttered schools : race, community, and school closures in American cities - Duncan-Shippy, Ebony M. (Research on African American education., 2019)
Since the late 1990s, mass school closures have reshaped urban education across the United States. Popular media coverage and research reports link this resurgence of school closures in major cities like Chicago and Philadelphia to charter school expansion, municipal budget deficits, and racial segregation. However, this phenomenon is largely overlooked in contemporary education scholarship. Shuttered Schools: Race, Community, and School Closures in American Cities (Information Age Publishing) is an interdisciplinary volume that integrates multiple perspectives to study the complex practice of school closure--an issue that transcends education. Academics, practitioners, activists, and policymakers will recognize the far-reaching implications of these decisions for school communities.Shuttered Schools features rigorous new studies of school closures in cities across the United States. This research contextualizes contemporary school closures and accounts for their disproportionate impact on African American students. With topics ranging from gentrification and redevelopment to student experiences with school loss, research presented in this text incorporates various methods (e.g., case studies, interviews, regression techniques, and textual analysis) to evaluate the intended and unintended consequences of closure for students, families, and communities. This work demonstrates that shifts in the social, economic, and political contexts of education inform closure practice in meaningful ways. The impacts of shuttering schools are neither colorblind nor class-neutral, but indeed interact with social contexts in ways that reify existing social inequalities in education.